Task syndromes: linking personality and task allocation in social animal groups. (6th February 2021) - Loftus, J C; Perez, A A; Sih, A
Abstract: Studies of eusocial insects have extensively investigated two components of task allocation: how individuals distribute themselves among different tasks in a colony and how the distribution of labor changes to meet fluctuating task demand. While discrete age- and morphologically-based task allocation systems explain much of the social order in these colonies, the basis for task allocation in non-eusocial organisms and within eusocial castes remains unknown. Building from recent advances in the study of among-individual variation in behavior (i.e., animal personalities), we explore a potential mechanism by which individuality in behaviors unrelated to tasks can guide the developmental trajectories that lead to task specialization. We refer to the task-based behavioral syndrome that results from the correlation between the antecedent behavioral tendencies and task participation as a task syndrome. In this review, we present a framework that integrates concepts from a long history of task allocation research in eusocial organisms with recent findings from animal personality research to elucidate how task syndromes and resulting task allocation might manifest in animal groups. By drawing upon an extensive and diverse literature to evaluate the hypothesized framework, this review identifies future areas for study at the intersection of social behavior and animal personality. Abstract : Consistent individual differences in seemingly task-independent behavioral tendencies can potentially drive task allocation in animal groups. Recent studies have found that animal groups containing behaviorally diverse individuals can outperform less diverse groups. In reviewing the literature, we find support for the hypothesis that efficient task allocation driven by variation among groupmates in task-independent behavior contributes to the success of diverse groups, and we generate predictions for future exploration of this phenomenon.